The positive effect of phosphogypsum-supplemented composts on potato plant growth in the field and tuber yield. (15th September 2017) - Kammoun, Mariem; Ghorbel, Imen; Charfeddine, Safa; Kamoun, Lotfi; Gargouri-Bouzid, Radhia; Nouri-Ellouz, Oumèma
Abstract: The production of phosphoric acid from phosphate rock leads to an industrial by-product called phosphogypsum (PG). One ton of phosphoric acid generates 5 tons of PG that is frequently stocked near the production units. Several attempts were made to test PG valorization via soil amendment because of its phosphate, sulphate and calcium content. In this study, the use of PG in composting was envisaged. Composts were produced by mixing olive oil wastes and spent coffee grounds. Two concentrations of PG, 10% (A10 ) and 30% (A30 ), were tested in composting substrate in addition to control compost without PG (AT ). After 8 months of fermentation, the resulting composts were used in field experiments using nine different treatments conducted to evaluate the potential use of these PG-containing composts in potato plant (cv. Spunta) cultivation. Plants were grown in the field and the different composts (AT, A10 and A30 ) were added as fertilizer and compared to commercial compost and cattle manure. During the culture period, a number of physiological (dry weight, chlorophyll content, tuber yield) and biochemical parameters (antioxidant activities, mineral content, starch and protein content) were followed. Similarly, chlorophyll content was measured in plants cultivated on commercial or PG supplemented composts. An increment of 55.17% in potato yield was recorded with the use of A30 the compost. Collectively, these data reveal the positive impact of the addition of PG in composting which may be adopted as a strategy for PG valorization and its use for the production of high quality edible products. Highlights: Composting may be adopted as a strategy for Phosphogypsum (PG) valorization. The co-composting of PG with Olive Waste was used in potato plant cultivation. Co-Composting of PG with agricultural wastes can provide good quality composts. The addition of PG in composting has a positive impact on potato productivity.